2017
DOI: 10.3847/1538-4357/aa70a0
|View full text |Cite
|
Sign up to set email alerts
|

First Results from BISTRO: A SCUBA-2 Polarimeter Survey of the Gould Belt

Abstract: We present the first results from the B-fields In STar-forming Region Observations (BISTRO) survey, using the Sub-millimetre Common-User Bolometer Array2 camera, with its associated polarimeter (POL-2), on the James Clerk Maxwell Telescope in Hawaii. We discuss the survey's aims and objectives. We describe the rationale behind the survey, and the questions thatthe survey will aim to answer. The most important of these is the role of magnetic fields in the star formation process on the scale of individual fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 112 publications
7
86
0
Order By: Relevance
“…Analysis of the observations has shown that the filaments may have a nearly constant radius ∼ 0.1 pc. Polarimetry surveys of the Gould belt indicated that the large-scale magnetic field direction can be both perpendicular and parallel to the axis of a filament (Ward-Thompson et al 2017). These findings rise a question how the different filaments form.…”
Section: Introductionmentioning
confidence: 89%
“…Analysis of the observations has shown that the filaments may have a nearly constant radius ∼ 0.1 pc. Polarimetry surveys of the Gould belt indicated that the large-scale magnetic field direction can be both perpendicular and parallel to the axis of a filament (Ward-Thompson et al 2017). These findings rise a question how the different filaments form.…”
Section: Introductionmentioning
confidence: 89%
“…The POL-2 observations used in this analysis were originally presented by Ward-Thompson et al (2017), and form part of the JCMT BISTRO Large Program. We refer readers to that work for a detailed description of the data reduction, and summarize the key points here.…”
Section: Observationsmentioning
confidence: 99%
“…Faint 'striations' are seen in the low-density molecular gas parallel to the magnetic field direction, suggesting that material is accreting onto filaments along magnetic field lines (Sugitani et al 2011;Palmeirim et al 2013;Matthews et al 2014). Observations of high-mass star-forming regions have shown behaviour qualitatively similar to that in low-mass starforming regions (Ward-Thompson et al 2017). However, in order to accurately constrain the role of magnetic fields in high-mass filaments, and to understand the connection between the roles of magnetic fields in low-and high-mass star formation, detailed studies of the strength of magnetic fields in high-mass filaments, and their contribution to the energy balance of high-mass star-forming regions, must be undertaken.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations